2013
DOI: 10.1121/1.4774273
|View full text |Cite
|
Sign up to set email alerts
|

A free-field method to calibrate bone conduction transducers

Abstract: Bone conduction communication systems employ a variety of transducers with different physical and electroacoustic properties, and these transducers may be worn at various skull locations. Testing these systems thus requires a reliable means of transducer calibration that can be implemented across different devices, skull locations, and settings. Unfortunately, existing calibration standards do not meet these criteria. Audiometric bone conduction standards focus on only one device model and on limited skull loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Previous studies have shown that sound transmits differently at different parts of the human skull (Snidecor et al, 1959;Gripper et al, 2007;McBride et al, 2008a;McBride et al, 2008b;Osafo-Yeboah et al, 2009;Stanley and Walker, 2009;McBride et al, 2011;Pollard et al, 2013;Tran et al, 2013). Recordings made with bone microphones at different locations are likely to enhance and degrade different parts of the speech spectrum, and this can be relevant for speech intelligibility (Snidecor et al, 1959;Acker-Mills et al, 2005;Acker-Mills et al, 2006;McBride et al, 2011;Tran et al, 2013).…”
Section: Device Placement and Background Noisementioning
confidence: 94%
See 1 more Smart Citation
“…Previous studies have shown that sound transmits differently at different parts of the human skull (Snidecor et al, 1959;Gripper et al, 2007;McBride et al, 2008a;McBride et al, 2008b;Osafo-Yeboah et al, 2009;Stanley and Walker, 2009;McBride et al, 2011;Pollard et al, 2013;Tran et al, 2013). Recordings made with bone microphones at different locations are likely to enhance and degrade different parts of the speech spectrum, and this can be relevant for speech intelligibility (Snidecor et al, 1959;Acker-Mills et al, 2005;Acker-Mills et al, 2006;McBride et al, 2011;Tran et al, 2013).…”
Section: Device Placement and Background Noisementioning
confidence: 94%
“…The playback level of speech was pre-calibrated to perceptually match the loudness of speech playing from a freestanding Infinity Studio Monitor TM 150 loudspeaker, measuring 70 dB SPL at the location of the head with the listener absent (see also Pollard et al, 2013). This level was chosen to make the listening task sufficiently challenging to avoid ceiling effects.…”
Section: Playback Methodsmentioning
confidence: 99%
“…To ensure that each listener heard the headphone and BC headset signals as loud as the loudspeaker signals, a loudness matching procedure was used to set the intensity of both devices (Pollard, Tran, & Letowski, 2013). For the headphones, three listeners who did not participate in the study performed this procedure before the experimental sessions began.…”
Section: Methodsmentioning
confidence: 99%
“…Sound intensity for the loudspeaker trials was preset to approximately 65 dB (A) as measured by a sound level meter located at ear level from the middle of the room where the listener’s head would be centered. To ensure that each listener heard the headphone and BC headset signals as loud as the loudspeaker signals, a loudness matching procedure was used to set the intensity of both devices (Pollard, Tran, & Letowski, 2013). For the headphones, three listeners who did not participate in the study performed this procedure before the experimental sessions began.…”
Section: Methodsmentioning
confidence: 99%
“…This test is performed using the direct method inside the anechoic chamber and a room that has a background noise around 45 dB separately (Pollard, Tran, Letowski, & Resources, 2013). After that, the result is compared between the two rooms.…”
Section: Measurement Of Insulation Levelmentioning
confidence: 99%